1990
DOI: 10.1002/em.2850160108
|View full text |Cite
|
Sign up to set email alerts
|

In vitro transcription assay of ozonated T7 phage dna

Abstract: Address reprint request to Y.S. Chung, Universite de Montreal, DCpartement de Sciences Biologiques, CP 6128 Succ. A. Montreal (Que) H3C 3J7, Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Ozone can effectively kill bacteria and has the advantage that contact times for antimicrobial action are typically 4-5 times shorter than for chlorine (Zuma et al 2009a;Zuma and Jonnalagadda 2010). Previous investigations have found that ozone treatment can damage the cell membrane (Scott and Lesher 1963;Murray et al 1965;Kim et al 1999;Guzel-Seydim et al 2004;Cho et al 2010), facilitate protein denaturation and also destroy enzyme activity (Hinze et al 1987;Mehlman and Borek 1987;Takamoto et al 1992;Komanapalli and Lau 1996) and the nucleic acids of microbes (Scott and Lesher 1963;Roy et al 1981;Mura and Chung 1990;Hunt and Mariñas 1999). Other studies have investigated the effect of ozone on the spore inner membrane of B. subtilis (Cortezzo et al 2004;Young and Setlow 2004) and spore morphologies of Bacillus atrophaeus and Geobacillus stearothermophilus (Mahfoudh et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone can effectively kill bacteria and has the advantage that contact times for antimicrobial action are typically 4-5 times shorter than for chlorine (Zuma et al 2009a;Zuma and Jonnalagadda 2010). Previous investigations have found that ozone treatment can damage the cell membrane (Scott and Lesher 1963;Murray et al 1965;Kim et al 1999;Guzel-Seydim et al 2004;Cho et al 2010), facilitate protein denaturation and also destroy enzyme activity (Hinze et al 1987;Mehlman and Borek 1987;Takamoto et al 1992;Komanapalli and Lau 1996) and the nucleic acids of microbes (Scott and Lesher 1963;Roy et al 1981;Mura and Chung 1990;Hunt and Mariñas 1999). Other studies have investigated the effect of ozone on the spore inner membrane of B. subtilis (Cortezzo et al 2004;Young and Setlow 2004) and spore morphologies of Bacillus atrophaeus and Geobacillus stearothermophilus (Mahfoudh et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…1992; Komanapalli and Lau 1996) and the nucleic acids of microbes (Scott and Lesher 1963; Roy et al. 1981; Mura and Chung 1990; Hunt and Mariñas 1999). Other studies have investigated the effect of ozone on the spore inner membrane of B. subtilis (Cortezzo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone modified nucleic acids in vitro , with thymine being more sensitive than cytosine and uracil (Scott 1975;Ishizaki and others 1981). In another study, ozone opened the circular plasmid DNA and reduced its transforming ability, produced single-and double-strand breaks in plasmid DNA (Hamelin 1985), and decreased transcription activity (Mura and Chung 1990). Studying E. coli, l' Herault and Chung (1984) found that ozone may induce mutations.…”
Section: Mechanism Of Microbicidal Action Of Ozonementioning
confidence: 99%
“…Studies have been undertaken to elucidate the action mechanism of ozone. Researchers have found that it can damage cell membranes (Scott & Lesher, 1963;Murray et al, 1965;Kim et al, 1999;GuzelSeydim et al, 2004;Cho et al, 2010), facilitate protein denaturation and enzyme activity decrease (Hinze et al, 1987;Mehlman et al, 1987;Takamoto et al, 1992;Komanapalli & Lau, 1996), as well as destroy the nucleic acids of microbes (Scott & Lesher, 1963;Roy et al, 1981;Mura & Chung, 1990; Hunt & Mariñas, 1999). Other studies have investigated the effect of ozone on the spore inner membrane of Bacillus subtilis (Young & Setlow, 2004;Cortezzo et al, 2004), and on the spore morphologies of Bacillus atrophaeus as well as Geobacillus stearothermophilus (Mahfoudh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%